Accidental Removal of a Carotid Endovascular Stent during Oropharyngeal Mass Biopsy. (4th January 2010) - Rameh, Charbel; Deveze, Arnaud; Lavieille, Jean-Pierre; Magnan, Jacques; Sanjuan, Melanie
Abstract : A 54-year-old male patient, with a history of a right mandibular adenocarcinoma, previously excised, and treated with post operative chemo- and radio-therapy, presented with a right oropharyngeal necrotic mass of several months duration. His history is pertinent for a right internal carotid endovascular stenting 2 years prior to presentation. During biopsy of his oropharyngeal lesion, a specimen of tissue was retrieved, with the carotid stent within. There was no bleeding. To the best of our knowledge, there is no such case reported in the literature. We present this case as a reminder on the importance and risks of radiation-induced necrosis and its distortion of the surrounding anatomy, especially in the presence of foreign bodies or protheses.